Mental health in Germany in the first weeks of the Russo-Ukrainian war - Gottschick, Cornelia; Diexer, Sophie; Massag, Janka; Klee, Bianca; Broda, Anja; Purschke, Oliver; Binder, Mascha; Sedding, Daniel; Frese, Thomas; Girndt, Matthias; Höll, Jessica; Michl, Patrick; et al. (BJPsych Open, 2023)
Anxiety disorders; depressive disorders; epidemiology; rating scales; statistical methodology